2021
DOI: 10.1038/s41598-021-90753-y
|View full text |Cite
|
Sign up to set email alerts
|

Good prediction of treatment responses to neoadjuvant chemoradiotherapy for esophageal cancer based on preoperative inflammatory status and tumor glucose metabolism

Abstract: To develop a tool for predicting pathologic complete response (pCR) after neoadjuvant chemoradiotherapy (neoCRT) in patients with esophageal cancer by combining inflammatory status and tumor glucose metabolic activity. This study included 127 patients with locally advanced esophageal cancer who had received neoCRT followed by esophagectomy from 2007 to 2016. We collected their neutrophil–lymphocyte ratio (NLR) and standardized uptake value (SUV) obtained from fluorodeoxyglucose positron emission tomography (PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Non-responders had higher postoperative pulmonary morbidity, a higher 30-day mortality rate, and a lower survival rate compared to those of histopathologic responders (p<0.001). pCR was an independent significant predictor for EC, and patients who achieved pCR had better progression free survival(PFS) and OS than those without pCR [40]. The results of this meta-analysis showed that NCRT can result in better pCR rates in patients with ESCC than those achieved with CRT (OR = 5.21, 95% CI:2.85-9.50, p<0.00001), which means that it can provide better survival benefits.…”
Section: Plos Onementioning
confidence: 79%
“…Non-responders had higher postoperative pulmonary morbidity, a higher 30-day mortality rate, and a lower survival rate compared to those of histopathologic responders (p<0.001). pCR was an independent significant predictor for EC, and patients who achieved pCR had better progression free survival(PFS) and OS than those without pCR [40]. The results of this meta-analysis showed that NCRT can result in better pCR rates in patients with ESCC than those achieved with CRT (OR = 5.21, 95% CI:2.85-9.50, p<0.00001), which means that it can provide better survival benefits.…”
Section: Plos Onementioning
confidence: 79%
“…Seventy-eight articles were included for full screening (31 congress abstracts, 47 original articles); 57 were excluded due to unclear description/criteria for groups and/or variables ( n = 34) or studies that did not assess PR and/or CR ( n = 23). Finally, we included 21 studies (20 original articles 21 40 and one study congress abstract 41 ). We identified 10 studies on biological immune and metabolic TME biomarkers without the presence of an 18 F-FDG-PET/CT scan (two studies on metabolic biomarkers, eight on immune biomarkers).…”
Section: Resultsmentioning
confidence: 99%
“…Three studies 26 , 32 , 37 were prospective and 18 studies were retrospective. 21 24 , 26 31 , 33 36 , 38 41 Eight studies assessed only EAC, 24 , 26 28 , 30 , 34 , 35 , 40 six studies assessed only ESCC, 21 , 23 , 25 , 36 38 and seven studies included both types. 18 21 , 27 , 35 , 37 …”
Section: Resultsmentioning
confidence: 99%
“…Several inflammatory indexes have been reported to be associated with pCR and prognosis after neoadjuvant therapy for esophageal cancer, such as lymphocyte (LY), 20 , 21 neutrophil to lymphocyte ratio (NLR), 21 , 22 platelet to lymphocyte ratio (PLR), 21 , 23 lymphocyte to monocyte ratio (LMR), 24 and systemic immune inflammation index (SII). 23 In this study, we explored the dynamics of inflammatory indexes at baseline, after two cycles of nICT and postoperative one month.…”
Section: Introductionmentioning
confidence: 99%